2002
DOI: 10.1007/s00431-002-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of a novel hexavalent DTPa-HBV-IPV/Hib vaccine compared to separate concomitant injections of DTPa-IPV/Hib and HBV vaccines, when administered according to a 3, 5 and 11 month vaccination schedule

Abstract: the new diphtheria-tetanus-acellular pertussis-hepatitis B virus-inactivated polio/ Haemophilus influenzae b vaccine administered at 3, 5 and 11 months of age was safe and at least as immunogenic as the comparator vaccines thus providing an effective and more comfortable option for this infant vaccination schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…In children vaccinated with 2 doses of DTPa-HBV-IPV/Hib at 3 and 5 months of age, 96.8% had anti-HBs antibodies ≥10 mIU/ml, increasing to 98.9% after the third dose at 11-12 months of age [11]. These results are similar to those observed when monovalent HBV is co-administered with DTPa-IPV/Hib at 3, 5 and 11-12 months [12].…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…In children vaccinated with 2 doses of DTPa-HBV-IPV/Hib at 3 and 5 months of age, 96.8% had anti-HBs antibodies ≥10 mIU/ml, increasing to 98.9% after the third dose at 11-12 months of age [11]. These results are similar to those observed when monovalent HBV is co-administered with DTPa-IPV/Hib at 3, 5 and 11-12 months [12].…”
Section: Introductionsupporting
confidence: 92%
“…Results of the primary vaccination study (study 031) conducted in 1998-1999 have been reported previously [12]. The phase 4 open, follow up and challenge study was conducted in 12 centres in Slovakia between 07 June 2010 and 26 November 2010 (113954, www.clinicaltrials.gov NCT01138098) according to Good Clinical Practice guidelines and the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8] Moreover, its immunogenicity profile was generally similar to that of currently available DTPa-based pentavalent vaccines plus monovalent HBV or Hib vaccines (DTPa-HBV-IPV plus Hib or DTPa-IPV Hib plus HBV vaccines).…”
Section: Immunogenicitymentioning
confidence: 73%
“…In Infanrix hexaÔ recipients, seroprotective antibody titers against diphtheria and tetanus toxoids and poliovirus type 1, 2 and 3 antigens were achieved in ‡95% of infants »1 month after primary vaccination [2][3][4][5][6] and in ‡99.3% of infants »1 month after booster vaccination (compared with ‡94.7% and 100% of infants who received comparator vaccines). [5][6][7][8] Vaccine response rates against the three pertussis antigens (pertussis toxoid [PT], filamentous haemagglutinin [FHA] and pertactin [PRN]) were ‡95.7% »1 month after primary vaccination [2][3][4][5][6] and ‡86.0% »1 month after booster vaccination (compared with ‡90.3% and 100% of infants who received comparator vaccines).…”
Section: Immunogenicitymentioning
confidence: 87%